Speaking Anxiety among the Fourth Semester Students of English Department at University - Yunita Sinaga; Dedi Sukma Wijaya (Journal of English Language and Education, 2026)
Speaking anxiety is considered one of the most significant psychological factors affecting students’ speaking performance in English as a Foreign Language (EFL) learning. High anxiety may reduce students’ confidence, participation, and oral communication ability in speaking classes. This study aimed to identify the levels of speaking anxiety experienced by the fourth semester students of English Department at Kutai Kartanegara University and determine the dominant aspect of anxiety experienced during Speaking Class. This research applied a descriptive quantitative design using a survey method. The participants of this study were 22 students selected through total population sampling. The instrument used was the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al. (1986), consisting of 33 questionnaire items. The findings revealed that most students experienced a moderate level of speaking anxiety, with a mean score of 94.76. Furthermore, test anxiety was identified as the dominant aspect of speaking anxiety, followed by communication apprehension and fear of negative evaluation. The study concluded that students’ speaking anxiety was primarily caused by evaluative classroom situations and performance pressure during Speaking Class.